Russula hainanensis (Russulaceae, Russulales), a new species from tropical China - Han, Yun-Xiao; Liang, Zhi-Qun; Jiang, Shuai; Zeng, Nian-Kai (Phytotaxa, 2022)
Russula hainanensis (Russulaceae, Russulales), a member of Russula subgenus Heterophyllidia section Ingratae, from Hainan, tropical China, is described as new based on morphological and phylogenetic evidence. An illustrated morphological description as well as comparisons with related species are presented.